Get the scoop, Geronimo! - Stilton, Geronimo (Stilton, Geronimo. Cavemice, 2015)
"Geronimo Stiltonoot and The Stone Gazette are in the running for the Stone Age Ratitzer: the award for the best prehistoric journalism! But their main competition is Sally Rockmousen, the ruthless host of Gossip Radio -- and she'll stop at nothing to win. Can Geronimo sniff out a scoop in time to defeat her?"--Back cover.